Surgical management of an infant with nonresolving pneumonia - Sumant Prabhudesai; Vishal Sawant; Sujoy Das; Bharati Sawant (Wolters Kluwer Medknow Publications, 2022)
We describe a 3-month-old baby who presented with a nonresolving pneumonia which failed to respond to antibiotic therapy. An underlying congenital pulmonary adenomatous malformation was suspected. On thoracotomy, she was found to have a tuberculous mediastinal abscess which was drained. Mediastinal abscess is a rare occurrence in childhood tuberculosis.